Research on the application of UAV airborne transient electromagnetic in the detection of shallow sliding surface. Issue 1 (February 2021) - Wang, Yong; Zhai, Songtao; Zhang, Xiaopei; Du, Lizhi
Abstract: In complex terrain conditions, how to achieve fast and efficient detection of the sliding surface is primary issue for the shallow landslide hazard investigation. In this paper, the UAV (Unmanned Aerial Vehicle) airborne transient electromagnetic method of Lengshui landslide in Fujian province was detecting a sliding surface. The comparison and analysis of resistivity data and borehole data show that the consistency of resistivity data and borehole geological stratification is good, and the three-dimensional distribution characteristics of the landslide can be inferred from resistivity data. Also, this paper determines the acquisition parameters of UAV airborne transient electromagnetic flight state and array types through experimental research, which has certain practical reference and guidance significance.